DECISION-MAKING BEHAVIOR OF LOAN RESTRUCTURING BASED ON INSTITUTIONAL LOGICS: CASE STUDY BANK PERKREDITAN RAKYAT INDUSTRY IN WEST JAVA REGION - Sugiarto Kasmuri; Elvia R. Shauki (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
This research examines the phenomena of loan restructuring decision behavior carried out by BPRs’ actors (loan officers or loan managers) in West Java Province. It is aimed to answer the research questions: why rural banks (BPRs) as institutional fields pay less attention to loan restructuring to recover the accounting losses from the provision of problem loans. According to Otoritas Jasa Keuangan (2017), 94 out of 290 BPRs in West Java Province did not feel eager to restructure the problem loans despite having a ratio of Non-Performing Loans (NPL) more than 5% threshold. The behavior itself could be motivated by both symbolic factors and material factors as carriers for their behavior. Two prior studies conducted by Micucci and Rossi (2010), Dardac, Barbu, and Boitan (2011) examined loan restructuring based on policies and its impact on banks as institutional but did not reveal the behavioral side of the restructuring decision-making proceed by an individual of loan managers and loan officers. Thus, this study is aimed at observing the individual motivation of actors symbolized by loan managers and loan officers in rural banks (BPRs) in West Java Province. The analysis of decision taken by loan officers or loan managers in this study uses an institutional logic basis which theory focuses on the logic of actors both individually or collectively in such a particular economic sector. The results explain that symbolic carriers (regulations and accounting standards) and material carriers (informal practices, routines, individual target, accounting practice difficulties) revealed the phenomena related the behaviour of actors’ (loan managers and loan officers) in BPR which put less attention on loan restructuring - as one of the credit risk mitigation for troubled debt. Second, there is similarity for actors to avoid the troubled debt restructuring due to some difficulties in recognizing loss occurred in the beginning period of restructuring.Keywords: And Accounting Practice, Behavior, Institutional Logics, Loss On Restructuring, Material Carriers, Motivation, Symbolic Carriers.